Character structure in Bakhtiar Ali's novel Jamshid Khani Mammam Ke Hamishe Ba Bai Deybard - Saeed, Dr.Zahir Ismail (Sulaimani Journal for Humanities, 2026)
This research entitled Character Structure in Bakhtiar Ali's Novel Jamshid Khani Mammam, Who Always Was Carried Away by the Wind, is an attempt to reveal the nature of the character in this novel. The reason for choosing the subject of the character in this study is due to the vitality of this novel and the choice of the characters that Bakhtiar Ali has portrayed in this novel. Through the characters, the author presents the experience of the Kurdish nation and politicians in South Kurdistan.
Keywords: Jamshid Khan; Main Character; SubCharacter; Barostin Character; Barnastin Character; Real Character; Fantasy Character